INTENSITAS PERILAKU PENGGUNA E-LEARNING SYSTEM DENGAN MODEL UTAUT - Sari, Fatma; Purnamasari, Susan Dian (Universitas Bina Darma, 2013)
This study aims to determine behavioral intention in the use of e-learning system using models UTAUT. The phenomenon underlying the research is: It is not yet optimal use of e-learning by students information systems in the learning process, not yet optimal socialization of the existence of e-learning, so that is not maximized and yet utilization measurability of the impact of using e-learning for lecturers.This study is limited in its scope: analysis of the influence of performance expectancy, effort expectancy, social influence on behavioral intention in the use of e-learning on the lecturer in the University of Bina Darma. results showed that Performance Expectancy of Behavioral Intention in the use of e-learning system had no significant effect while the Effort Expectancy and Social Influence on Behavior Intention in the use of e-learning system. Keywords: E-learning System, Models UTAUT, Performance Expectancy, Effort Expectancy, and Social Influence